2022
DOI: 10.3390/biomedicines10061459
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Aspects and Molecular Targets of Autophagy to Control Pancreatic Cancer Management

Abstract: Pancreatic cancer (PC) begins within the organ of the pancreas, which produces digestive enzymes, and is one of the formidable cancers for which appropriate treatment strategies are urgently needed. Autophagy occurs in the many chambers of PC tissue, including cancer cells, cancer-related fibroblasts, and immune cells, and can be fine-tuned by various promotive and suppressive signals. Consequently, the impacts of autophagy on pancreatic carcinogenesis and progression depend greatly on its stage and conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 132 publications
0
1
0
Order By: Relevance
“…This example is but one of many complex roles for autophagy that have been described in PDAC initiation and development (reviewed in [169]). Clinical trials of autophagy inhibitors in PDAC have yet to show efficacy; one phase II trial found that hydroxychloroquine monotherapy reduced autophagy but had negligible efficacy in patients with previously treated metastatic PDAC [170].…”
Section: Nutrient Recycling and Autophagymentioning
confidence: 99%
“…This example is but one of many complex roles for autophagy that have been described in PDAC initiation and development (reviewed in [169]). Clinical trials of autophagy inhibitors in PDAC have yet to show efficacy; one phase II trial found that hydroxychloroquine monotherapy reduced autophagy but had negligible efficacy in patients with previously treated metastatic PDAC [170].…”
Section: Nutrient Recycling and Autophagymentioning
confidence: 99%
“…In order to create DMVs derived from ER membranes, SARS-CoV-2 can divert autophagy flux. This creates niches for immune evasion and viral RNA replication [44].…”
Section: Modulation Of Autophagy During Sars-cov-2 Infectionmentioning
confidence: 99%
“…ROS secreted from mitochondria is removed by cell antioxidant systems, and various cell components are oxidatively damaged due to hydroxyl radical (•OH) formation [ 12 , 13 ]. Low and moderate level of ROS is a critical mediator of metabolism and inflammation, but an excessive level of ROS contributes to apoptosis or autophagy containing H 2 O 2 − sensitive pathways, respectively [ 14 , 15 , 16 , 17 ]. Notably, excessive amounts of ROS are highly toxic to cells.…”
Section: Production Of Reactive Oxygen Species (Ros) Due To Oxidative...mentioning
confidence: 99%